Evaluation of PCC Load Balancing for Dual ISP Networks: Enhancing Throughput and Traffic Stability - Bustomi Bustomi; Muhlis Tahir (Universitas Hamzanwadi, 2026)
Multi-ISP network management often experiences imbalanced traffic distribution and decreased connection stability despite having adequate bandwidth capacity. Previous studies indicate that load balancing methods such as PCC are effective in traffic distribution; however, they remain limited to implementation aspects, with constraints in analyzing network processing efficiency and inconsistencies in results across various testing conditions. This study aims to empirically evaluate the effectiveness of PCC integrated with failover in improving dual ISP network performance. It employs a controlled experimental design with a comparative approach before and after implementation in a real network environment. The measured parameters include throughput, traffic distribution, connection stability, and packet rate, which are analyzed using a quantitative measurement-based comparative approach. The results show an increase in download throughput from 15–18 Mbps to 36–41 Mbps (±130–150%) and upload throughput from 14–17 Mbps to 36–40 Mbps (±120–140%), more balanced traffic distribution, and a significant reduction in packet rate, indicating improved network processing efficiency. The integration of failover also ensures service continuity without significant disruption. This study provides empirical evidence that a connection-based load balancing approach not only improves traffic distribution but also enhances network processing efficiency, extends previous research, and is relevant for multi-ISP networks with dynamic traffic.